Determinant of securitization spread in Malaysia - Bakri, Mohammed Hariri; Sufian, Fadzlan; Abdul Hamid, Baharom; Ismail, Shafinar (Universiti Malaysia Sarawak, 2018)
Malaysian firms have been reported to be involved in Asset-Backed Securities since 1986 when Cagamas Bhd was the pioneer in the field. This research aims to examine the factors influencing spread in Malaysia’s securitization market. In order to provide a test of stability and a choice of model, the multicollinearity test was conducted by providing information on the degree of correlation between the explanotary variables used in the multivariate regression analysis. Ordinary Least Square method was used for baseline, and panel data analysis was applied during the study period (2004-2012) for a more robust check of the analysis. The data were obtained from 90 non-financial firms or institutions and the number of observations carried out was 387. The results show that four determinants influence or contribute to the primary market spread and are statistically significant in developing securitisation in Malaysia. It can be concluded that loan to value, maturity, debt and crisis significantly contribute to the determinant primary market spread. From five hypotheses, two hypotheses support that the determinants have a relationship with primary market spread. The result will act as a model and benchmark for other ASEAN countries to use as Malaysia was resilient during the subprime mortgage crisis in 2008. Policy makers can use this study to execute the timing and quantum of issuance securitisation. The other findings of this study have considerable policy relevance. It could be stated that the higher the risk reflects the higher the spread of the firm, especially when there is lower credit rating during crisis periods and higher debt. Therefore, the role of a firm is to reduce the risk in order to reduce the spread, and simultaneously reduce the cost of financing by finding alternative sources of funding. The continued success of the Malaysian securitisation firms depends on their efficiency in using their resources and the competitiveness of the firms.